Vacuolar sorting receptor for seed storage proteins in Arabidopsis thaliana - Shimada, Tomoo (National Academy of Sciences, 2003)
The seeds of higher plants accumulate large quantities of storage protein. During seed maturation, storage protein precursors synthesized on rough endoplasmic reticulum are sorted to protein storage vacuoles, where they are converted into the mature forms and accumulated. Previous attempts to determine the sorting machinery for storage proteins have not been successful. Here we show that a type I membrane protein, AtVSR1/AtELP, of Arabidopsis functions as a sorting receptor for storage proteins. The atvsr1 mutant missorts storage proteins by secreting them from cells, resulting in an enlarged and electron-dense extracellular space in the seeds. The atvsr1 seeds have distorted cells and smaller protein storage vacuoles than do WT seeds, and atvsr1 seeds abnormally accumulate the precursors of two major storage proteins, 12S globulin and 2S albumin, together with the mature forms of these proteins. AtVSR1 was found to bind to the C-terminal peptide of 12S globulin in a Ca(2+)-dependent manner. These findings demonstrate a receptor-mediated transport of seed storage proteins to protein storage vacuoles in higher plants.